Generic classification for the Gasteruptiinae (Hymenoptera: Gasteruptiidae) based on a cladistic analysis, with the description of two new Neotropical genera and the revalidation of Plutofoenus Kieffer - Macedo, Antonio Carlos Cruz (Zootaxa, 2009)
Gasteruptiinae is the largest Gasteruptiidae subfamily, with circa 400 species that have been grouped into the worldwide Gasteruption Latreille. Based on a cladistic analysis with 43 morphological characters, 40 ingroup taxa representing all biogeographic regions, and seven outgroups (four Hyptiogastrinae, two Aulacidae and one Evaniidae), I confirm the monophyly of Gasteruptiinae and Gasteruption and recognize three exclusively Neotropical small genera: Plutofoenus Kieffer (revalidated) (southern South America), Spinolafoenus Macedo n. gen. (Chile) and Trilobitofoenus Macedo n. gen. (Central and South America). Gasteruption, supported by four synapomorphies, remains the most speciose genus in the subfamily. The four Gasteruptiinae genera are keyed and described. Seven species are keyed and described or redescribed: Plutofoenus chaeturus (Schletterer) n. comb., P. edwardsi Turner, P. paraguayensis (Schrottky), Spinolafoenus ruficornis (Spinola) n. comb., Trilobitofoenus alvarengai Macedo n. sp., T. plaumanni Macedo n. sp. and T. sericeus (Cameron) n. comb. (lectotype designated).